2016
DOI: 10.3847/0004-637x/818/2/191
|View full text |Cite
|
Sign up to set email alerts
|

THE 7Be ii RESONANCE LINES IN TWO CLASSICAL NOVAE V5668 SGR AND V2944 OPH

Abstract: We report spectroscopic observations of the resonance lines of singly ionized 7 Be in the blue-shifted absorption line systems found in the post-outburst spectra of two classical novae -V5668 Sgr (Nova Sagittarii 2015 No. 2) and V2944 Oph (Nova Ophiuchi 2015). The unstable isotope, 7 Be, should has been created during the thermonuclear runaway (TNR) of these novae and decays to form 7 Li within a short period (a half-life of 53.22 days). Confirmations of 7 Be are the second and the third ones following the fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 25 publications
8
68
3
1
Order By: Relevance
“…In conclusion, atomic data and observations indicate that the strong and wide absorption feature close to λ 3130 in V838 Her can be only partially explained as a blend of common iron curtain absorption lines. This agrees with the studies of recent novae by Tajitsu et al (2015Tajitsu et al ( , 2016 and Molaro et al (2016), who found only a minor contribution of singly-ionized metal transitions to this feature.…”
Section: The 7 Be II 3132å Absorption Feature In Early Spectrasupporting
confidence: 93%
See 1 more Smart Citation
“…In conclusion, atomic data and observations indicate that the strong and wide absorption feature close to λ 3130 in V838 Her can be only partially explained as a blend of common iron curtain absorption lines. This agrees with the studies of recent novae by Tajitsu et al (2015Tajitsu et al ( , 2016 and Molaro et al (2016), who found only a minor contribution of singly-ionized metal transitions to this feature.…”
Section: The 7 Be II 3132å Absorption Feature In Early Spectrasupporting
confidence: 93%
“…It is worth mentioning that the depletion of oxygen and the significant enrichment in heavier elements such as sulphur and aluminium was considered as an observational evidence that breakout from the CNO cycle may have occurred in a massive ONe WD (Schatz 2004;Schwarz et al 2007;Glasner & Truran 2009). However, modeling of the outburst of V838 Her (Downen et al 2013;Champagne et al 2014) indicated a massive (1.34-1.35 M ) ONe WD, without com- Tajitsu et al (2015Tajitsu et al ( , 2016 are corrected here for the decay of 7 Be. References are: (1) Tajitsu et al (2015); (2) Molaro et al (2016), (3) Izzo et al (2018) and (4) pelling evidence for breakout (T peak in the TNR close to 3 × 10 8 K).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, thanks to the use of high-resolution spectrographs, we were for the first time able to observe the presence of 7 Li in the early spectra of novae V1369 Cen (Izzo et al 2015) and V5668 Sgr (Wagner et al in preparation, Izzo et al in preparation). In addition, evidence of large quantities of 7 Be ii has also been reported, after ∼ 60 days from the outburst, for the carbon-oxygen (CO) novae V339 Del (Tajitsu et al 2015), V2944 Oph (Tajitsu et al 2016) and V5668 Sgr Molaro et al (2016). In the latter case, the observation of unsaturated narrow components allowed an accurate 7 Be abundance determination, which led the authors to suggest that classical novae are one of the main lithium factories in the Galaxy.…”
Section: Introductionmentioning
confidence: 95%
“…2 (V5668 Sgr). A spectrum from the High Dispersion Spectrograph of the Subaru Telescope taken at day 63 after maximum has been discussed by Tajitsu et al (2016) who reported the presence of 7 Be ii in this Nova, and also in V2944 Oph. At early epochs the spectra of the Nova show several broad emission lines of neutral hydrogen and other permitted transitions of neutral or singly ionised species often accompanied by sharp and blue-shifted multiple absorption components reaching blue edge velocities of ≈ -2300 km s −1 .…”
Section: Introductionmentioning
confidence: 99%